Exploring the Alignment Between Higher Education Specializations and Labor Market Needs in Azerbaijan - Nasirova, Elnara (ADA University, 2025)
This study examines the extent to which higher education specializations in Azerbaijan correspond with the changing requirements of the labor market and how this impacts students’ academic and professional development and career perspectives as well. While national regulation on specialization classification establishes admission to postgraduate programs, it restricts students from pursuing interdisciplinary or alternative academic paths, which leads to becoming a critical issue in a rapidly evolving labor market that increasingly values applied knowledge and adaptability. By employing a mixed-methods approach, the research combines data from 51 survey participants with semi-structured interviews conducted with three experts from certain state entities, alongside a graduate and a student from specific areas of specialization. The research is grounded in Human Capital Theory, which states that investing in education enhances the employability of graduates by equipping them with relevant knowledge and competencies. Findings disclose a partial alignment between academic specializations and labor market demands. Even though full degree programs are still highly valued in Azerbaijani society, which affects salaries and job placement, universities frequently find it difficult to meet the skill demands of the market. While specific exemptions exist, such as in MBA programs, international studies, and civil service development programs, broader flexibility remains limited. The study offers some recommendations to address the raised issue—both for universities, for better preparing their students for the labor market, and for graduates, for improving their chances of obtaining desired jobs. It provides suggestions for future research that will investigate and enhance the understanding of this issue.
Keywords: Higher education -- Economic aspects.; Education and employment -- Azerbaijan.; Labor market -- Requirements.; College graduates -- Employment.; Vocational guidance -- University students.; Education -- Labor supply and demand.